FORMATION OF MINERAL PROTECTIVE COATINGS FROM SOLUTIONS OF SILICONE COMPOUNDS: CURRENT STATE OF THE ART - TYKHONOV, PLATON; MYRONYUK, OLEKSIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article discusses the potential for enhanced protection of metal substrates against corrosion by mineral film formers. Corrosion resistance, self-cleaning ability, and antimicrobial properties are what superhydrophobic mineral-based surfaces can offer. Compared to traditional organic matrices, which are vulnerable to environmental factors and unstable during operation, the use of alkoxysilane sol-gel coatings eliminates these disadvantages and increases compliance with the principles of green chemistry and sustainable development. The main advantages of mineral coatings are effective adhesion to the substrate due to the formation of covalent Me-O-Si bonds, Si-O-Si siloxane chains that act as a physical barrier against corrosive agents, the possibility of using in a wide temperature range, and relative “eco-friendliness” in production. The aim of the article is to analyze the optimal approaches to obtaining mineral protective films from solutions of organosilicon compounds with improved corrosion resistance due to surface texturing by introducing additives. The chemical transformations of hydrolysis and polycondensation of alkoxysilanes and their binding to the substrate are determined. The influence of pH, temperature, reaction time, solvent, concentration, catalysis, and substituents on the formation and properties of the film is presented. The methods of possible surface treatment of the substrate are indicated. The influence of morphological and energy characteristics of the surface on water-repellent properties, which is an important factor in corrosion resistance, is reviewed. The use of different types of hydrophobic micro- and nano-additives and their influence on the superhydrophobic and anticorrosive properties of alkoxysilane surfaces is shown, which is confirmed by the corresponding wetting and rolling angles and electrochemical tests. In particular, the use of modification of the fillers themselves and increasing resistance by self-healing. The challenges, problems and prospects for the use of such protective coatings are also described. As a result, a systematic review of approaches to obtaining mineral protective coatings was conducted and the use of micro/nano additives as protective superhydrophobic surface formers was highlighted.
Keywords: superhydrophobicity; alkoxysilanes; sol-gel; mineral film formers; polycondensation; corrosion resistance